The Critical Study of the Omnibus Bill on Job Creation Based on John Rawls View on Justice - Kukuh Tejomurti; Sukarmi Sukarmi (Universitas Negeri Semarang, 2020)
This study aimed to analyze the critical study of The Omnibus Bill On Job Creation based on John Rawls view On Justice. The Government and the House of Representatives ratified the Omnibus Bill on Job Creation through a plenary meeting on October 5, 2020. This is more focused on improving economic growth or investment but does not pay attention to increase the protection and competence of human resources. The type of this research uses normative legal research, legal research that is conducted based on law and regulation, and library material. Related to this type of research, the approach used in this paper is legal, a conceptual approach, and a historical approach. According to the result of research, it can be concluded that the rules of the Omnibus Bill on Job Creation has implications for the imbalance of position between companies and workers and do not provide legal certainty for workers' protection. According to John Rawls, a justice will not sacrifice the rights of some people for the benefits enjoyed by others. Based on the opinion of John Rawls, we can know that if we sacrifice the rights of others for profit is not right. The cooperation based on a work agreement should be of benefit to all parties. These are benefits that can provide welfare to one another. Companies do not need to pay as high as company directors, but companies must be transparent about finances.